Citizen Heritage and Geoheritage : A Sampling Campaign for Cosmogenic 36Cl Surface Exposure Dating of Glacial Deposits in Mt Parnassus National Park, Greece - Pavlopoulos, Kosmas (2022)
A sampling campaign for 36Cl dating of Quaternary moraines was conducted in June 2021 with an open call on social media for participation of citizens regardless of their background. The organization was jointly realized by geoscientists and mountain hiking professional guides. A multi-beneficial collaboration both for science and geoheritage was achieved which resulted in a very efficient sampling campaign. At the same time participants and professional guides were actively involved in scientific research thus gaining a deeper understanding of the geoheritage of Mt Parnassus National Park.